Dynamic modeling of vortex induced vibration wind turbines. (June 2018) - Chizfahm, A.; Yazdi, E. Azadi; Eghtesad, M.
Abstract: This paper studies the dynamic modeling of four configurations of vortex-induced vibrations of a bladeless wind turbine (BWT). The BWTs consist of a bluff body mounted on a flexible structure in the flow field. The shape of the bluff body and its mounting structure are different among the proposed BWTs. The Euler-Bernoulli beam theory and the Galerkin procedure are used to derive a nonlinear distributed-parameter model for the BWTs under a fluctuating lift force due to periodically shedding vortices. The derived dynamic model is validated through comparison with a 3D CFD-FEM numerical simulation. The effects of the wind speed on the induced lift force, turbine deflection, and generated power of four BWTs are investigated. It is verified that the amplitude of the vibrations of the BWT increases significantly when the vortex shedding is synchronized with the structural oscillations. The results show that, while conic BWTs have a higher performance at post-synchronization region (i.e. high wind speeds), the right circular cylinder BWTs exhibits a better performance at pre-synchronization region (i.e. low wind speeds). Graphical abstract: Image 1 Highlights: The governing equation of a bladeless wind turbine (BWT) is derived. The model has been validated through a 3D CFD-FEM numerical simulation. The effects of the wind speed on the performance of BWT are investigated. The conic BWTs have a higher performance at high wind speeds. The right circular cylinder BWTs exhibits a better performance at low wind speeds.